Potential of Guava (Psidium guajava L.) Leaf Extract as Antioxidant Agent in Natural Mud Mask Formulation - Mardiana, Rosa; Salsabila, Salsabila; Lidyawati, Lidyawati (Universitas Serambi Mekkah, 2025)
This study aimed to determine the antioxidant activity of guava (Psidium guajava L.) leaf extract and its potential use as an active ingredient in a natural mud mask formulation. The research employed an experimental laboratory design with a single factor, namely variations in guava leaf extract concentrations (0 g, 3 g, and 5 g). The antioxidant activity was evaluated using the DPPH method, and the results were expressed as IC₅₀ values. The findings revealed that the antioxidant activity increased significantly with the concentration of guava leaf extract. Formula F0 (without extract) exhibited very weak activity with an IC₅₀ value of 210 ppm, while F1 (3 g extract) and F2 (5 g extract) showed very strong activities with IC₅₀ values of 1.165 ppm and 0.541 ppm, respectively. These results indicate that guava leaf extract has very strong antioxidant potential, comparable to vitamin C (IC₅₀ = 0.481 ppm). Therefore, the formulation containing 5 g of guava leaf extract is considered optimal for developing a safe, effective, and environmentally friendly natural clay mask with high antioxidant potential.